-7(3+x)=-91

Simple and best practice solution for -7(3+x)=-91 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7(3+x)=-91 equation:


Simplifying
-7(3 + x) = -91
(3 * -7 + x * -7) = -91
(-21 + -7x) = -91

Solving
-21 + -7x = -91

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '21' to each side of the equation.
-21 + 21 + -7x = -91 + 21

Combine like terms: -21 + 21 = 0
0 + -7x = -91 + 21
-7x = -91 + 21

Combine like terms: -91 + 21 = -70
-7x = -70

Divide each side by '-7'.
x = 10

Simplifying
x = 10

See similar equations:

| 9x=4-65 | | 4a-13=99 | | 5(x-4)=4(x+6) | | 3x-5y=-12 | | -3(3)+5x=-4 | | 6(7+2x)=78 | | 5x+9y=-1 | | 2.6y+8.3=4.6y-3.4 | | 2x^2+10x-2=0 | | 2(a+5)=6a-6 | | 5x^2+13x=6 | | 4d+7=11 | | 2x-12+2x=4x-12 | | -2(t-8)-(t+7)=8 | | 3(n+2)=6n-9 | | 2x-(5x-3)=5(x-3)-2(x-3) | | y+11=23 | | 2=6h+20 | | 2(s+1)=6s-6 | | 8x+5=6x+33 | | 4n+11=27 | | 4(x-1)=-4+4x | | 4(x+2)+6=34 | | -26=-7x-2 | | 5m+7+6m=29 | | -4(4x-8)=-128 | | 3x-9=7+2x-x | | 24y-10=20y-17 | | 3x+4y=167 | | 3x+4=12x-7 | | 6(x+3)-6=24 | | -x+5+2x=14 |

Equations solver categories